NEWS OF HASHTAG MOVEMENT 2019 REPLACE PRESIDENT Framing Analysis Robert N. Entman on Mediaindonsia.com Period September 2018-Januari 2019 - Diah Agung Esfandari; Muhammad Izzuddin Alqosam (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2020)
The Internet and Media are the two things that make it easy for people to get and produce information. With the presence of the Internet and the media, making media companies take advantage of their presence in producing and disseminating information, like mediaindonesia.com. The purpose of this study was to find out how Media Indonesia framed the news about hashtag movement #2019gantipresiden period September 2018-January 2019. This study used Robert N. framing analysis with qualitative research methods and constructivism paradigms. The results of this study indicate that Mediaindonesia.com has a view that tends to be neutral and objective. The information shown in this study is that the value carried in the news about hashtag movement #2019gantipresiden that raises a split in the community that has different supporters in the 2019 election competition. #2019gantipresiden also brings bad value to the current leader, because of name and news which was highlighted by the action was leaning towards an attempt to overthrow the President's leadership.